Eagle threat: significant and control techniques according to al-Hadith perspective - Md Ariffin, Mohd Farhan; Ahmad, Khadher; Ramli, Mohd Anuar; Abdullah, Mohammad Naim (Universiti Teknologi MARA, Perlis, 2016)
Eagle is an animal that quite known among animal breeders. Eagle is a ferocious predator and possesses strong claws. Eagle’s dominant natures that like to threat domestic animal affected the source of food supply and human income. In Islam, these types of animals dubbed as pests. Therefore, early preventive measures in the form of knowledge is very important in order to understand the concept of “interaction with pests” well. Significantly, Prophet Muhammad SAW has warned on threat posed by pest cluster including eagle in his set saying. Thus, this article strives to peel regarding eagle description with the methods to interact with pests through al-Hadith discussions. This case is important to provide guidance to society regarding harms that able to be incarnated by particular animal and also the most efficient control techniques according to Prophetic tradition without marginalizing animal exclusive rights.